O RPG como estratégia metodológica para a mobilização do conteúdo de clima urbano na formação inicial de professores de Geografia - Souza, Layanne Almeida de (2020)
The gaps present in teacher training are mainly composed of difficulties in organizing the curricular structure that tends to offer disciplines that do not dialogue among themselves, with fragmented and diverse contents. This is the result of a historical-philosophical construction of knowledge from the Cartesian view of the world, in which it is fragmented to try to understand the whole and this has been brought into education. This fragmented position of disciplines and contents is being increasingly discussed in the educational context, especially when methodological teaching strategies are mentioned. The present work seeks to analyze the potentialities of using the Role-Playing Game - RPG as a methodological strategy for the mobilization of urban climate content in the initial training of Geography teachers. The teaching strategies allow greater interaction between students, content and experience and have been the subject of numerous research and debates in events in recent decades. Geography has been no different, especially in the teaching of the physical-natural climate component, which is the focus of this research. Studies on methodological strategies for climate education are mostly related to practical activities, experiments and representations of atmospheric and climatic events. The research does not deviate from this parameter, however, a specific methodological strategy is presented: the RPG. Thus, this research seeks to understand whether the use of RPG, as a methodological strategy, contributes to the construction of concepts about the urban climate and enables the development and expansion of foundations from the pedagogical knowledge of content in the initial training of Geography teachers. Therefore, in this study, it is necessary to understand how the urban climate content can be mobilized from the use of RPG as a methodological strategy, which theoretical-methodological and conceptual bases permeate the research, the discussions about climate phenomena in urban areas and the didactic-pedagogical route to forward the RPG proposal with the students. The research was carried out focusing on the initial training of Geography teachers. In November 2019, an activity entitled "RPG as a methodological strategy for teaching urban climate" was held at the Federal University of Goiás. The activity was directed to students who completed the course of Geography - Licenciatura frequent in the subject of Methodologies for Teaching Geography II. The condition for delineating the participants was in function of the necessity that the subjects of the research were at the end of graduation and had concluded the disciplines of Climatology and Urban Geography. The choice of the subject of Geography II Teaching Methodologies was based on the discussion of methodologies for building knowledge about the physical-natural components such as soil, relief, climate, water, vegetation and others. For the game, the research subjects defined the name of their characters and developed their interpretations from problem situations occurring in the urban context, with direct involvement of the climate. The proposal to play RPG focusing on the mobilization of a specific content was carried out with the research subjects and allowed them to contribute to the conceptual construction and theoretical-methodological basis on the content of urban climate and the themes and content that went through the game. The RPG also contributed to reflect on the importance of using imagination and creation in the teaching and learning process.